PENGARUH TUJUAN ANGGARAN DAN MOTIVASI KERJA TERHADAP REALISASI ANGGARAN DAN DAMPAK TERHADAP KINERJA OPERASIONAL (Studi pada Organisasi Perangkat Daerah di Kota Langsa) - Agustina Nurul Fajriah; Afrah Junita; Tri Herlinda (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2025)
This research is motivated by the importance of the role of budget goals and work motivation in increasing budget realization and operational performance in Langsa City Regional Apparatus Organizations (OPD). The realization of optimal budgets is an indicator of the effectiveness of regional financial management, but is often hampered by lack of targeted planning and low employee motivation. The research population was Langsa City OPD with a sample size of 65 respondents selected using purposive sampling techniques. Data was collected through a questionnaire which was measured using an ordinal scale, analyzed using path analysis using SPSS. The research results show that budget objectives and work motivation have a significant positive effect on budget realization and operational performance. Operational performance has a significant effect on budget realization and mediates the relationship between budget objectives and work motivation on budget realization. This research has limitations in that this research was only conducted at 13 OPDs in Langsa City with 65 respondents, so the results cannot be generalized to all local governments. The research uses quantitative based on respondents' perceptions, the results depend on the honesty and objectivity of respondents' answers to the questionnaire, the research variables only cover four main constructs, namely budget objectives, work motivation, budget realization, and operational performance, while there are still other factors that may have an influence such as leadership style, organizational culture, and internal monitoring systems which are not included in this research model.